Innate immune receptors for cross-presentation: The expanding role of NLRs. (September 2019) - Corridoni, Daniele; Simmons, Alison
Highlights: PRRs temporally control cross-presentation during acute vs. chronic pathogen handling. NLRs signal in close proximity to phagosomal and endosomal membranes. Current status of NLR-dependent regulation of MHC class antigen presentation. Abstract: A critical role of pattern recognition receptors (PRRs) is to influence adaptive immune responses by regulating antigen presentation. Engagement of PRRs in dendritic cells (DCs) increases MHC class I antigen presentation and CD8 + T-cell activation by cross-presented peptides but the molecular mechanisms underlying these effects are not completely understood. Studies looking at the role of PRRs in cross-presentation have been largely limited to TLRs but the role of other PRRs such as cytosolic nucleotide-binding oligomerization domain-like (NOD-like) receptors remains particularly enigmatic. Here we discuss recent evidence of the role of PRRs on cross-presentation and consider how cytosolic NLR-associated pathways, such as NOD2, may integrate these signals resulting in effective adaptive CD8 + T cells responses.